The Influence of Career Development and Perceived Organizational Support (POS) on Employee Retention Through Employee Performance at PT. Graha Agung Perkasa - Mustabsyiroh Kumala; Yuniardi Rusdianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of career development and perceived organizational support (POS) on employee retention through employee performance at PT. Graha Agung Perkasa. The type of research carried out in this research is quantitative. The population in this study were employees from PT. Graha Agung Perkasa, totaling 100 respondents. The sample collection technique used the Slovin formula which obtained 50 respondents. The research results showed that career development had a significant effect on employee retention, perceived organizational support (POS) had a significant effect on employee retention, career development had a significant effect on employee performance, perceived organizational support (POS) has an effect but is not significant on employee performance, and employee retention has a significant effect on employee performance.